War as a Genre. A Look into Painting - Pezzini, Isabella (E|C, 2024)
Since antiquity, war, and in particular its crucial event, battle, have also been considered a spectacle: memorial and celebratory, in memory of the blood cost to one’s history/identity; one’s valor; the pride of one’s lineage. Or an illustrative-educational spectacle useful to fix the crucial moments of a past or forthcoming battle, to illustrate historical, mythological and biblical episodes, to train in the art of war and prepare future fighters and keep their readiness and courage alive. Observing the spread of genre painting on this subject confirms this, helps us to distinguish the recurring traits of a crystallization of the event, distributed in recognizable elements, of its formal grammar progressively disengaged from the actual events of arms, and characterized by a strong character of decoration and ornamentation, however alienating this may appear to our sensibility. The occasion of this essay is also useful for a broader reflection on the concept of genre in painting, sub specie semiotics.